(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The cause and formulation of the problem, the purpose of the work. The effect of alternating magnetic field on vegetative reactions is studied insufficiently and requires additional research. Vegetative reactions under the influence of different climatic and geographical conditions in different ethnic groups have not been sufficiently studied either. The purpose of the work is to study the effects of alternating magnetic field on the vegetative nervous system and to study vegetative reactions to different climatic and geographical conditions in Egyptian and Ugro-Finnic ethnic groups. Methods: The following methods were used: electro-magnetic, analytical, spectral, wavelet, mathematical analysis, probabilistic, experimental. Results: Changes in the variability criteria under the influence of alternating magnetic field during long-term exposure were identified in the study. In particular, the index of activity of regulatory systems (IARS) for a group of people exposed to alternating magnetic field for 14 or more years is 3.5 points, that is, it is between moderate functional and pronounced functional stress, which is higher than in groups of people who have worked for fewer years and have been exposed to alternating magnetic field; maximum adaptive loads fall on people exposed to alternating magnetic field for 11–13 years; vegetative reactions indices of these people exceed the normalized limits. The study has made it possible to determine the averaged effective value of magnetic induction B = 500, mlTl in the cabin of the metro car with asynchronous traction motors, in motor cars of the above-ground metro. It was established that the working day for locomotive brigades of the metro with such a level of magnetic induction should not exceed 4 hours per shift, so that the body has time to fully recover. It was established that under the influence of alternating magnetic field factor rotating with a frequency from 0 to 140 Hz, an average person undergoes significant changes in the activity of regulatory systems, in particular, the index of activity of regulatory systems (IARS) changes significantly. Studies of vegetative reactions under the influence of different climatic and geographical conditions in Egyptian ethnic groups revealed that a change from the relatively warm type of climatic conditions (WTCC) and cool type of climatic conditions (CTCC) to the dry type of climatic conditions (DTCC) causes in these ethnic groups a decrease of the following parameters: Coefficient of comparative activity of the parasympathetic and sympathetic divisions of the ANS; Coefficient (relative value) of the predominance of the parasympathetic division over the sympathetic; Activity of the parasympathetic division of the ANS; Activity of the autonomous regulatory loop; Relative level of activity of the parasympathetic division of the regulation; The influence of the parasympathetic division of the ANS; Normalized integral index (NIP); Stress index of regulatory systems. No significant impact of the considered types of climatic conditions was revealed on the condition of the cervical spine. The index of activity of regulatory systems (IARS) slightly increases according to the scheme: CTCC, WTCC, and DTCC. Studies of vegetative reactions under the influence of different climatic and geographical conditions in the Ugro-Finnish ethnic groups revealed that, as compared to the CTCC and WTCC, the DTCC promotes an increase of the following parameters: Salivary retardation ratio and pancreatic functions; Index of activity of regulatory systems (IARS); And contributes to the decrease of the following: The effects of the parasympathetic division of the ANS; The coefficient of comparative activity of the parasympathetic and sympathetic divisions of the ANS; Coefficient (relative value) of the predominance of the parasympathetic division over the sympathetic; Stage of the state of the upper cervical spine. As compared to the CTCC and DTCC, the WTCC in the considered ethnic groups contributes to the stabilization of the following: Index of activity of regulatory systems (IARS); Coefficient of comparative activity of the parasympathetic and sympathetic divisions of the ANS. As compared to the WTCC, the CTCC in the considered ethnic groups contributes to the following: Increase of the index of activity of regulatory systems (IARS); Decrease of the coefficient of comparative activity of the parasympathetic and sympathetic divisions of the ANS. It is revealed that in case of influenza: The relative level of activity of the parasympathetic division of regulation increases significantly; The index of activity of regulatory systems (IARS) increases; and the influence of the parasympathetic division of the ANS is reduced. Conclusion: As a result of scientific research, the following goals were achieved: The effect of an alternating magnetic field on the vegetative nervous system was determined—it leads to a weakening of regulatory systems after 11 years of exposure to this factor. It was revealed that when exposed to an alternating magnetic field rotating with a frequency from 0 to 140 Hz, an average person undergoes significant changes in the activity of regulatory systems. It was recommended, according to the requirements of Sanitary Regulations and Norms SanPiN 2.2.4.1191-03, taking into account the revealed physiological reactions to a rotating alternating magnetic field, that the duration of the working day for locomotive crews operating on rolling stock and persons exposed to alternating magnetic field should be reduced to 4 hours per day. It was established that under the influence of different climatic and geographical conditions in the Egyptian ethnic groups, DTCC, as compared to the WTCC and CTCC, causes a decrease in a number of physiological reactions in these ethnic groups. The index of the activity of regulatory systems (IARS) slightly increases according to the scheme: CTCC-WTCC-DTCC. It has been established that under the influence of different climatic and geographical conditions in the Ugro-Finnish ethnic groups, the DTCC, as compared to the CTCC and WTCC, contributes to a change in a number of physiological reactions, in particular, an increase in the activity index of regulatory systems (IARS). It has been established that in the case of influenza, the variability criteria—the relative level of activity of the parasympathetic division of regulation—increase significantly; the index of activity of regulatory systems (IARS) increases; and the influence of the parasympathetic division of the ANS is reduced. The materials are of practical value for scientists studying the influence of magnetic fields on human physiology, as well as studying vegetative reactions to different climatic and geographical conditions in different ethnic groups.